SARS-CoV-2 and SARS-CoV Spike-Mediated Cell-Cell Fusion Differ in Their Requirements for Receptor Expression and Proteolytic Activation - Hörnich, Bojan F.; Grosskopf, Anna K.; Schlagowski, Sarah; Tenbusch, Matthias; Kleine-Weber, Hannah; Neipel, Frank; Stahl-Hennig, Christiane; Hahn, Alexander S. (Journal of Virology, 2021)
Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) infects cells through interaction of its spike protein (SARS2-S) with angiotensin-converting enzyme 2 (ACE2) and activation by proteases, in particular transmembrane protease serine 2 (TMPRSS2). Viruses can also spread through fusion of infected with uninfected cells. We compared the requirements of ACE2 expression, proteolytic activation, and sensitivity to inhibitors for SARS2-S-mediated and SARS-CoV-S (SARS1-S)-mediated cell-cell fusion. SARS2-S-driven fusion was moderately increased by TMPRSS2 and strongly by ACE2, while SARS1-S-driven fusion was strongly increased by TMPRSS2 and less so by ACE2 expression. In contrast to that of SARS1-S, SARS2-S-mediated cell-cell fusion was efficiently activated by batimastat-sensitive metalloproteases. Mutation of the S1/S2 proteolytic cleavage site reduced effector cell-target cell fusion when ACE2 or TMPRSS2 was limiting and rendered SARS2-S-driven cell-cell fusion more dependent on TMPRSS2. When both ACE2 and TMPRSS2 were abundant, initial target cell-effector cell fusion was unaltered compared to that of wild-type (wt) SARS2-S, but syncytia remained smaller. Mutation of the S2 cleavage (S2') site specifically abrogated activation by TMPRSS2 for both cell-cell fusion and SARS2-S-driven pseudoparticle entry but still allowed for activation by metalloproteases for cell-cell fusion and by cathepsins for particle entry. Finally, we found that the TMPRSS2 inhibitor bromhexine, unlike the inhibitor camostat, was unable to reduce TMPRSS2-activated cell-cell fusion by SARS1-S and SARS2-S. Paradoxically, bromhexine enhanced cell-cell fusion in the presence of TMPRSS2, while its metabolite ambroxol exhibited inhibitory activity under some conditions. On Calu-3 lung cells, ambroxol weakly inhibited SARS2-S-driven lentiviral pseudoparticle entry, and both substances exhibited a dose-dependent trend toward weak inhibition of authentic SARS-CoV-2.IMPORTANCE Cell-cell fusion allows viruses to infect neighboring cells without the need to produce free virus and contributes to tissue damage by creating virus-infected syncytia. Our results demonstrate that the S2' cleavage site is essential for activation by TMPRSS2 and unravel important differences between SARS-CoV and SARS-CoV-2, among those, greater dependence of SARS-CoV-2 on ACE2 expression and activation by metalloproteases for cell-cell fusion. Bromhexine, reportedly an inhibitor of TMPRSS2, is currently being tested in clinical trials against coronavirus disease 2019. Our results indicate that bromhexine enhances fusion under some conditions. We therefore caution against the use of bromhexine in high dosages until its effects on SARS-CoV-2 spike activation are better understood. The related compound ambroxol, which similarly to bromhexine is clinically used as an expectorant, did not exhibit activating effects on cell-cell fusion. Both compounds exhibited weak inhibitory activity against SARS-CoV-2 infection at high concentrations, which might be clinically attainable for ambroxol.
CRIS-Team Scopus Importer:2021-04-30
Keywords: cell-cell fusion; COVID-19; SARS-CoV-2; spike; TMPRSS2; virus entry